General overview of the physical education in Israel [Articol] - Shama/Daniel, Einas (CEP USM, 2022)
The current article addresses the issues of the physical education in Israel, with specific attention on people with disabilities. Physical education is a core subject in the education system which is taught from first grade till 12th grade. Physical education teachers can initiate programs and activities in the field. School principals and physical education teachers are requested to submit in writing proposals for carrying out initiatives during the school year to the inspectors of physical education of the districts. Examples of initiatives: physical education week, sports classes, sports days, programs to promote an active and healthy lifestyle, peak days, class consolidation days centered on sports activity and transition programs related to physical education. The assessment of students’ achievements in classes should be carried out by the physical education teachers as part of the teaching, learning and evaluation processes.

Prezentul articol abordează problemele educației fizice în Israel, cu o atenție specială asupra persoanelor cu dizabilități. Educația fizică este o materie de bază în sistemul de învățământ care se predă din clasa I până în clasa a XII-a. Profesorii de educație fizică pot iniția programe și activități în domeniu. Directorii de școli și profesorii de educație fizică sunt rugați să înainteze în scris inspectorilor de educație fizică ai raioanelor propuneri de realizare a inițiativelor în cursul anului școlar. Exemple de inițiative: săptămâna educației fizice, cursuri de sport, zile sportive, programe de promovare a unui stil de viață activ și sănătos, zile de consolidare a clasei centrate pe activitatea sportivă și programe de tranziție legate de educația fizică. Examinarea realizărilor elevilor la ore trebuie efectuată de profesorii de educație fizică ca parte a predării, învățării și evaluării.
PREZENTARE GENERALĂ A EDUCAȚIEI FIZICE ÎN ISRAEL
Keywords: disability; physical education; teacher; achievements; learning; dizabilitate; educație fizică; profesor; realizări; învățare